A model and a methodology for the systematization of continuous improvement of logistics processes in world-class companies - Afonso, Paulo (2019)
Currently, it is fundamental for world-class organizations to implement effective continuous improvement processes which ask for significant and sustainable cost reduction programs. However, there is a lack of models and methodologies that support and validate continuous improvement in organizations. Its application in the logistics operation is particularly important because, currently, it is a determining factor of competiveness and differentiation, affecting significantly the profitability of organizations. In this investigation, an innovative model of continuous improvement based on costs has been developed and implemented; it is structured on three main steps: (1) a definition of cost management responsibilities, (2) establishing a relationship between financial performance indicators and operational indicators and (3) a dynamic generation of a continuous cycle of continuous improvement. Its implementation results also in a three level maturity model (A-C). The model was developed and implemented in a benchmark logistics department of one of the most important first tier suppliers of the automotive industry. The studied company made possible the implementation of the model in its fullness (level C), since the logistics department is in a high maturity level of the cost management and performance measurement process. This model can be replicated in other companies, departments and supply chains that want to reduce the costs proactively through really effective and efficient continuous improvement processes.